Negotiating the Boundaries of Belonging The Intricacies of Naturalisation in Germany - Witte, Nils (Studien zur Migrations- und Integrationspolitik,, 2018)
Nils Witte explores Turkish migrants' destigmatization strategies and investigates their legal and symbolic motives for naturalisation. Using mixed methods and unique data the author shows that Turkish migrants' inclination to naturalise would be stronger if they were allowed to retain their former citizenship and if they were recognized as symbolic members of German society. Minority members enjoy expansive rights as permanent residents and many are entitled to hold German citizenship. However, they often experience symbolic exclusion making symbolic membership a rare motive for naturalisation. Contents • Naturalisation in a Post-National World • Theorizing Legal and Symbolic Membership • Survey Results: Symbolic and Legal Membership • Qualitative Interviews: Stigmatization and Destigmatization Target Groups • Researchers and students of sociology, ethnography, and political theory who deal with migration and integration • Practitioners in the field of integration policies, commissioners for integration The Author Nils Witte is research assistant at the Karlsruhe Institute of Technology.